Strategi Guru Pendidikan Agama Islam dalam Pendidikan Karakter pada Siswa Kelas VIII SMP Tjokroaminoto Kecamatan Nanggung Kabupaten Bogor - Firdaos, Muti (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Character education for students is something that is very important to do continuously. This is done because of the current era of increasingly sophisticated development and the increasing influence of technology, especially for teenagers who are still unstable who need guidance and roles from parents, teachers and people around them. The formulation of the problem in this research is what is the character of class VIII students at Tjokroaminoto Middle School, Nanggung District, Bogor Regency, what are the strategies of Islamic Religious Education teachers in character education for class VIII students at Tjokroaminoto Middle School, Nanggung District, Bogor Regency, what are the supporting and inhibiting factors for Islamic Religious Education teachers' strategies in character education for class VIII students at Tjokroaminoto Middle School, Nanggung District, Bogor Regency. The purpose of this research is to determine the character of class VIII students at Tjokroaminoto Middle School, Nanggung District, Bogor Regency, to determine the strategies of Islamic Religious Education teachers in character education for class VIII students at Tjokroaminoto Middle School, Nanggung District, Bogor Regency, to determine the supporting and inhibiting factors for Islamic Religious Education teacher strategies in education. character of class VIII Tjokroaminoto Middle School students. Nanggung District, Bogor Regency. This type of research is a type of field research. Currently the approach used is a qualitative approach. Apart from that, the data collection methods in this research are observation, interviews and text. Meanwhile, researchers used descriptive analysis in data analysis. The results of this research show: First: Tjokroaminoto Middle School students have a positive attitude towards categories. These traits and attitudes include liking congregational prayers, daytime prayers, reading the Koran, respecting teachers and elders, and wanting to help each other, being honest and happy to talk to friends, and being kind to other people when study online. And before you study from home... Second: the strategies of Islamic Religious Education teachers in character education for students include: Mujahadah/training, habituation and giving incentives, teacher example and character education which is included in the learning process. Third: supporting factors for character education include: family factors, community environment and madrasah environment, while inhibiting factors for character education include internal factors: children who have been born since childhood due to lack of parental supervision and external factors: the influence of the era of globalization in the form of electronic media and social media which can have a negative impact on students in influencing students' character education.